2013
DOI: 10.1016/j.addbeh.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor gene variants interact with attention deficient hyperactive disorder symptoms to predict smoking trajectories from early adolescence to adulthood

Abstract: Objective To examine the association of single nucleotide polymorphisms (SNPs) of the CHRNB3 (rs13280604) and CHRNA6 (rs892413) nicotinic acetylcholine receptor (nAChR) genes and symptoms of attention deficit hyperactivity disorder (ADHD) in predicting smoking patterns from early adolescence to adulthood. Method A longitudinal cohort of 1137 unrelated youths from the National Longitudinal Study of Adolescent Health provided responses to four surveys from Waves I to IV, and a genetic sample in Wave III. Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thus, a third more focused hypothesis generated by those explorations involves epigenetic modulation of cholinergic or nicotinic receptor functioning. This focus may be particularly intriguing in light of the recent interest in those receptors' role in prefrontal cortical function, impulsivity, and attention (Lee, Fuemmeler, McClernon, Ashley-Koch, & Kollins, 2013;Ohmura, Tsutsui-Kimura, & Yoshioka, 2012;Sterley, Howells, & Russell, 2014;Wallace & Bertrand, 2013), recent genetic findings related to ADHD and cholinergic receptor genes (Williams et al, 2012), and interest in the role of nicotinic receptor intervention as an effective and novel treatment target for ADHD in animal and human trials (Bain et al, 2012;Potter, Dunbar, Mazzulla, Hosford, & Newhouse, 2014). ADHD status in the children from whom saliva was analyzed in this study was very well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a third more focused hypothesis generated by those explorations involves epigenetic modulation of cholinergic or nicotinic receptor functioning. This focus may be particularly intriguing in light of the recent interest in those receptors' role in prefrontal cortical function, impulsivity, and attention (Lee, Fuemmeler, McClernon, Ashley-Koch, & Kollins, 2013;Ohmura, Tsutsui-Kimura, & Yoshioka, 2012;Sterley, Howells, & Russell, 2014;Wallace & Bertrand, 2013), recent genetic findings related to ADHD and cholinergic receptor genes (Williams et al, 2012), and interest in the role of nicotinic receptor intervention as an effective and novel treatment target for ADHD in animal and human trials (Bain et al, 2012;Potter, Dunbar, Mazzulla, Hosford, & Newhouse, 2014). ADHD status in the children from whom saliva was analyzed in this study was very well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…While undoubtedly many factors contribute to this relationship, increasing evidence suggests that differences in attention processes and ADHD symptoms may be related to genetic variants in genes encoding nicotinic receptor subunits. Lee, Fuemmeler, McClernon, Ashley-Koch, and Kollins (2013) found a significant interaction between single nucleotide polymorphisms of CHRNB3 and ADHD where the AA variant and the ADHD symptom of inattention were associated with greater increase in the level of cigarette smoking across adolescence. The study also reported differences in cigarette smoking associated with variants of CHRNA6.…”
Section: Nicotine’s Effects On Adhdmentioning
confidence: 92%
“…Apart from early-subjective responses to tobacco, there exist many other ND-related phenotypes where the CHRNB3–CHRNA6 gene cluster may play an important role, such as smoking status (never smoking versus ever smoking), 35 smoking trajectories from early adolescence to adulthood, 45 and various ND endophenotypes such as ‘novelty seeking' 53 or ‘drive.' 37 In addition, smoking cessation is of great interest, because it is the ultimate goal of studying tobacco addiction and any other smoking-related phenotypes.…”
Section: Nd-related Phenotypesmentioning
confidence: 99%